Penggunaan Media Ajar Power Point untuk Meningkatkan Pembelajaran IPS di Sekolah Dasar - Nuraini, Aulia; Habibah, Rayna Iesha; Zahirah, Salwa Naurah; Rustini, Tin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
In this era of rapid globalization, education was required to continue to follow current developments, for example in the use of teaching media, especially in integrated social studies learning. One of the teaching media that was widely used was power point. Therefore, the aim of this research was to determine the effect of using PowerPoint as a teaching medium in improving social studies learning in elementary schools. The research method used was library research, namely by studying or collecting in-depth information and data through various literature, books, notes, other references, as well as relevant previous research results, to get answers. The use of power point teaching media can increase students’ motivation in learning and understanding social studies learning material. In this era of rapid globalization, education was required to continue to follow current developments, for example in the use of teaching media, especially in integrated social studies learning. One of the teaching media that was widely used was power point. Therefore, the aim of this research was to determine the effect of using PowerPoint as a teaching medium in improving social studies learning in elementary schools. The research method used was library research, namely by studying or collecting in-depth information and data through various literature, books, notes, other references, as well as relevant previous research results, to get answers. The use of power point teaching media can increase students’ motivation in learning and understanding social studies learning material.